The relationship between risk and return of listed companies in colombo stock exchange: special reference to hotels and travels sector - Mayuri, T.; Brintha, P.; Thanashanthy, T. (University of Jaffna, 2016)
Risk and return are fundamentally linked, the greater an investment's potential to achieve higher returns, the greater the risk associated with it. It is very important aspect in the financial management. Portfolio management will involve the various investments such as many different types of financial assets. Risk involved in such investment & derived from them. The necessity of well organized hotels and travels sector is realized in every country's economical development. This research is aimed to analysis the Risk & Return of hotels and travels sector in Sri Lanka for the period of 2010 to 2014.In this study, 19 listed hotel and travel companies are taken as a sample by using random sampling for the purpose of data analysis. The hypotheses are examined with help of Pearson's correlation and regression analysis. This study considers earning yield as independent variable and annual earnings per share return on asset and return on equity as dependent variable where as firm size and leverage are controlling variables. Data was collected from listed company's annual reports and journals. As a result of the analysis it could be seen that positive and significant correlation between the risk and return. It leads a high risk on the investor's fund to earn high return of Hotel and travel sector. The findings of the study will be useful for investors and practitioners
Keywords: Risk; Return; Earning yield; Return on equity; y, hotel and travels